2016
DOI: 10.1055/s-0042-100910
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Cancer: a Review of Current Knowledge

Abstract: Diabetes mellitus (DM), one of the most common life-threatening illnesses worldwide, is a group of metabolic diseases, characterized by sustained hyperglycemia. The global prevalence of diabetes mellitus among adults reached 387 millions in 2014 and is still rising. It is suggested there is a strong association between diabetes mellitus (especially type 2 diabetes mellitus) and carcinogenesis. The possible biological links between diabetes mellitus and cancer comprise hyperinsulinemia, hyperglycemia and fat-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
131
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(141 citation statements)
references
References 157 publications
2
131
0
8
Order By: Relevance
“…Most probably, Th17-cells were already activated in vivo during DM2, and exhibited functional exhaustion during additional stimulation ex vivo. Exposure to chronic inflammation may diminish effector functions of T-lymphocytes, which may impair protection against infections and cause predisposition to cancer, which is typical to diabetic patients [32][33][34]. It had also been shown that patients with DM2 are characterized by lower numbers of Th17, specific to infectious pathogens [35].…”
Section: Discussionmentioning
confidence: 99%
“…Most probably, Th17-cells were already activated in vivo during DM2, and exhibited functional exhaustion during additional stimulation ex vivo. Exposure to chronic inflammation may diminish effector functions of T-lymphocytes, which may impair protection against infections and cause predisposition to cancer, which is typical to diabetic patients [32][33][34]. It had also been shown that patients with DM2 are characterized by lower numbers of Th17, specific to infectious pathogens [35].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is characterized by sustained hyperglycemia and is associated with increased cancer risk in many settings, possibly through proliferative, anti-apoptotic, and metastatic activity [1]. Therefore, a series of studies have been performed to explore the associations of type 2 diabetes mellitus (T2DM), the common type in later life (~95% of all diabetic cases), with the risk and prognosis of cancers [1].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a series of studies have been performed to explore the associations of type 2 diabetes mellitus (T2DM), the common type in later life (~95% of all diabetic cases), with the risk and prognosis of cancers [1]. For breast cancer, the association was mainly observed in European females [2].…”
Section: Introductionmentioning
confidence: 99%
“…The association between diabetes and cancer is currently the focus of many clinical and basic research studies (1)(2)(3)(4)(5)(6). Epidemiologic analyses have shown an increased risk in type 2 diabetes of various epithelial cancers, including cancers of the breast, colon, bladder, pancreas, liver, and endometrium, as well as nonmelanoma skin cancer and more.…”
mentioning
confidence: 99%